The Integration of Auditory Intellectual Repetition Model Through the Development of Video Learning Media in Chemistry Practices Aa a Strategy for Adapting Technology in Learning - Maria Benedikta Tukan; Faderina Komisia; Maria Aloisia Uron Leba; Susana O. Leulaleng; Raymond F. Mesugama; Petronela Onika Lanmai (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to determine the validity of practicum-based learning video media integrated with the Auditory, Intellectually, Repetition (AIR) model and to describe students’ learning outcomes. The research method employed is developmental research using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research procedure includes the preparation stage, implementation stage, and final stage. The results of this study indicate that the developed media, based on validation by subject-matter experts in stages 1, 2, and 3, are categorized as very valid for field implementation, with a validation percentage of 95.6%. Furthermore, the feasibility of the learning media is also classified as very valid, indicating that it is appropriate for use in the learning context. The learning outcomes in the knowledge aspect obtained from 15 students after participating in the learning process are categorized as complete, with an average score of 85.66, which exceeds the minimum mastery criterion (MMC) of 70. This result is attributed to students’ active participation and full attention during the learning process, enabling them to understand the material well and successfully complete the given test. Overall, students’ learning outcomes are declared complete, with an average score of 85.7, which meets the school’s minimum mastery criterion of 70.